Interlaboratory comparison of heavy metal testing in animal diagnostic specimens and feed using inductively coupled plasma–mass spectrometry. (March 2020) - McGeehan, Steven; Baszler, Timothy; Gaskill, Cynthia; Johnson, Joseph; Smith, Lori; Raisbeck, Merl; Schrier, Nick; Harris, Heather; Talcott, Patricia
We compared inductively coupled plasma–mass spectrometry (ICP-MS) test results for the analysis of heavy metals (As, Ba, Cd, Hg, Pb, and Se) in pet foods and routine veterinary diagnostic specimens using intralaboratory and interlaboratory comparisons. Four laboratories, 1 principal laboratory and 3 collaborating laboratories, conducted instrument comparison (limit of detection [LOD], limit of quantification [LOQ], and linear dynamic range [LDR] on 24 data sets), in-house method comparison (accuracy and precision on 120 data sets), and interlaboratory comparison (reproducibility on 528 data sets using Horwitz equation analysis). Matrices tested included 2 types of pet food jerky treats (chicken and sweet potato), bovine blood, and bovine liver and kidney. The instrument comparison study confirmed that ICP-MS provided the sensitivity necessary for the analysis of all heavy metals tested at concentrations below the level of concern for routine diagnostic testing. The "in-house" method comparison samples, spiked at low (0.04 µg/g), medium (0.4 µg/g), and high (8.0 µg/g; note: the high validation level spike for mercury was 2 µg/g) concentration levels, indicated that ICP-MS can meet U.S. FDA acceptance criteria for both accuracy (90–105% recovery) and precision (< 6% coefficient of variation). The interlaboratory comparison studies showed that ICP-MS is a reproducible method for the analysis of heavy metals (HorRat value of 0.5–2.0) except for mercury in one laboratory, which used a different sample preparation method (open block rather than microwave digestion). Overall, our study showed that ICP-MS is a reproducible method for the analysis of heavy metals in spite of minor differences in methodology.